Studi tentang Peran Sosial Sekolah di SD Kanisius Sorowajan Yogyakarta - Purnama Dian; Emilya Tyas Wahyu Ningsih; Theresia Mardinah (Jurnal Penelitian Pendidikan Agama Katolik, 2023)
School is a good place to develop a community. Forming a society with high social awareness can be started by developing schools in the community. The collaboration between local community members and education observers in the Sorowajan Yogyakarta area has been fruitful. This study aims to describe the social role of Kanisius Sorowajan Elementary School in society. The research was conducted at SD Kanisius Sorowajan, Bantul, Yogyakarta. Researchers used a qualitative case study approach. The methods used in this research for data collecting were interviews and documentation. The data obtained was analyzed using techniques (in-depth analysis), namely by summarizing, categorizing, and interpreting the data into narratives. Informants or resource persons in this study were school principals, students, teachers, employees of Kanisius Sorowajan Elementary School, and members of the community around the school. The research was conducted from May to September 2022. The results showed that the social role of Kanisius Sorowajan Elementary School was found not only in its social activities but also in the school's active involvement in every aspect of the life of the community around the school. The social activities aforementioned were visiting sick residents, distributing groceries for the elderly, community members affected by Covid-19, community members in need, mourning, interfaith joint prayers, and ruwahan. Schools can support the community by providing locals for youth activities, arisan RT, tirakatan, alumni gatherings, Sunday School, wedding receptions, community Masses every Tuesday night, etc. while also providing mats, sound system, and sometimes assisting the society in repairing public streets.